Ureteral endometriosis: a rare and underdiagnosed cause of renal dysfunction - Yaramareddy, Swapna; Shankar, Kundavi; Kurien, Abraham; Varma, Thankam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Ureteral endometriosis is a serious localization of disease that can lead to urinary tract obstruction, hydroureteronephrosis and potential kidney loss. We describe three cases of ureteral endometriosis where there was documented renal function loss with subsequent workup and surgical intervention. Clinical suspicion and preoperative assessment may help with diagnosis and allows for a multidisciplinary pre-consultation. Surgical technique to treatment varies, but the goal is to salvage renal function and decrease disease burden. Laparoscopic surgical approach can be carried out successfully in the hands of an experienced laparoscopic surgeon. These cases illustrate varying surgical approaches tailored to management of ureteral endometriosis. Women in reproductive age presenting with pelvic pain diagnosed to have hydronephrosis must be adequately evaluated for ureteral endometriosis.